Isolation and Characterization of Salmonid Cd4+ T Cells - Sandino-Garcia, A; Imarai-Bahamonde, C; Maisey-Munoz, K; Valenzuela-Montenegro, B; Reyes-Cerpa, S; Toro-Ascuy, D; Montero, R (American Association of Immunologists, 2016)
This study reports the isolation and functional characterization of rainbow trout (Oncorhynchus mykiss) CD4-1+ T cells and the establishment of an IL-15-dependent CD4-1+ T cell line. By using Abs specific for CD4-1 and CD3ϵ it was possible to isolate the double-positive T cells in spleen and head kidney. The morphology and the presence of transcripts for T cell markers in the sorted CD4-1+CD3ϵ+ cells were studied next. Cells were found to express TCRα, TCRβ, CD152 (CTLA-4), CD154 (CD40L), T-bet, GATA-3, and STAT-1. The sorted CD4-1+ T cells also had a distinctive functional attribute of mammalian T lymphocytes, namely they could undergo Ag-specific proliferation, using OVA as a model Ag. The OVA-stimulated cells showed increased expression of several cytokines, including IFN-γ1, IL-4/13A, IL-15, IL-17D, IL-10, and TGF-β1, perhaps indicating that T cell proliferation led to differentiation into distinct effector phenotypes. Using IL-15 as a growth factor, we have selected a lymphoid cell line derived from rainbow trout head kidney cells. The morphology, cell surface expression of CD4-1, and the presence of transcripts of T cell cytokines and transcription factors indicated that this is a CD4-1+ T cell line. To our knowledge, this is the first demonstration of the presence of CD4-1+CD3ϵ+ T cells in salmonids. As in mammals, CD4-1+ T cells may be the master regulators of immune responses in fish, and therefore these findings and the new model T cell line developed will contribute to a greater understanding of T cell function and immune responses in teleost fish. Copyright © 2016 by The American Association of Immunologists, Inc.